Pilot Neonatal Screening Program for Central Congenital Hypothyroidism: Evidence of Significant Detection - Braslavsky, Debora Giselle (2017)
Background/Aim: Congenital hypothyroidism (CH) is a heterogeneous entity. Neonatal screening programs based on thyrotropin (TSH) determination allow primary CH diagnosis but miss central CH (CCH). CCH causes morbidity, alerts to other pituitary deficiencies, and is more prevalent than previously thought. We aimed at developing a pilot neonatal screening program for CCH detection. Patients and Methods: A prospective 2-year pilot neonatal screening study based on simultaneous dried blood specimen TSH and thyroxine (T4) measurements was implemented in term newborns aged 2-7 days. Those with T4 ≤4.5 μg/dL (-2.3 SDS) and TSH <10 mIU/L were recalled (suspicious of CCH) and underwent clinical and biochemical assessment performed by expert pediatric endocrinologists. Results: A total of 67,719 newborns were screened. Primary CH was confirmed in 24 (1: 2,821). Forty-four newborns with potential CCH were recalled (recall rate 0.07%) at a mean age of 12.6 ± 4.8 days. In this group, permanent CCH was confirmed in 3 (1: 22,573), starting L-T4 treatment at a mean age of 12.3 ± 6.6 days; 14 boys showed T4-binding globulin deficiency (1: 4,837); 24 had transient hypothyroxinemia (21 non-thyroidal illness and 3 healthy); and 3 died before the confirmation stage. According to initial free T4 measurements, CCH patients had moderate hypothyroidism. Conclusions: Adding T4 to TSH measurements enabled the identification of CCH as a prevalent condition and contributed to improving the care of newborns with congenital hypopituitarism and recognizing other thyroidal disorders.